If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9x + -16 = -1 Reorder the terms: -16 + -9x = -1 Solving -16 + -9x = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + -9x = -1 + 16 Combine like terms: -16 + 16 = 0 0 + -9x = -1 + 16 -9x = -1 + 16 Combine like terms: -1 + 16 = 15 -9x = 15 Divide each side by '-9'. x = -1.666666667 Simplifying x = -1.666666667
| 5(x-3)=3x+4+2(5-x) | | .4t+1.7=1.3 | | 8y^2+105y+13= | | -27-3x^2=0 | | 6+r=4 | | 5m-7=1+7m | | 5(4x-3)=-25 | | 4(x-2)=2(x+10) | | 152+2h=972 | | y-9+2=6 | | 21+5x=-34 | | 9+3.5g=11-.5g | | 9x+37=91 | | 7x-2(5x+9)=7-(11-11x) | | 69r+69= | | n-3(3)=14-4(3) | | 22(6-v)+6v=148 | | (x-2)*2=49 | | n-3(2)=14-4(2) | | 3v+6=7 | | 41c-41d= | | (a+1)*2=25 | | 7r-4r+5=9r+5-r | | 3x^2+18x+7=0 | | 0=(6-7x)10 | | (x-2)(y+3)=35 | | 2y+x=23 | | 5j-25=35 | | f(x)=x^4+x^3+x^2-9x-10 | | 8x-5=2x-5 | | 3-386+2= | | 4y+1y=13 |